2008
DOI: 10.1097/jcp.0b013e31817e63a5
|View full text |Cite
|
Sign up to set email alerts
|

Standard and Higher Dose of Olanzapine in Patients With Schizophrenia or Schizoaffective Disorder

Abstract: The objective of this study was to assess the dose-response relationship of standard and higher doses of olanzapine in a randomized, double-blind, 8-week, fixed-dose study comparing olanzapine 10 (n = 199), 20 (n = 200), and 40 mg/d (n = 200) for patients with schizophrenia or schizoaffective disorder and suboptimal response to current treatment. Patients meeting criteria for antipsychotic treatment resistance were excluded. Dose-response relationship was assessed by linear regression analysis with log-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 29 publications
3
53
1
2
Order By: Relevance
“…28 The largest fixed-dose study to date showed olanzapine 10 mg to be just as effective as 20 mg and 40 mg a day. 29 These observations of a low ceiling of effect tie in nicely with receptor occupancy studies suggesting saturation of receptors at low doses. 30 Thus, more is not better once a certain dose is reached, at least with antipsychotics used as single agents.…”
Section: Editorialsupporting
confidence: 58%
“…28 The largest fixed-dose study to date showed olanzapine 10 mg to be just as effective as 20 mg and 40 mg a day. 29 These observations of a low ceiling of effect tie in nicely with receptor occupancy studies suggesting saturation of receptors at low doses. 30 Thus, more is not better once a certain dose is reached, at least with antipsychotics used as single agents.…”
Section: Editorialsupporting
confidence: 58%
“…The mean doses of olanzapine used over the 3-year follow-up are consistent with those suggested in pharmacological guide- lines for the treatment of schizophrenia [2] , and the olanzapine median dose initiated at the baseline visit (10 mg) is consistent with the results of a randomised study that suggests this dose as the initial dose of choice for schizophrenia patients instead of higher doses (20 or 40 mg) [22] . Current results show that the frequency of dose adjustments decreases over time, which may refl ect achievement of the optimal dose for each patient.…”
Section: Discussion ▼mentioning
confidence: 76%
“…However, subsequent independent scrutiny of the design and data analysis of this study revealed serious flaws, leading to the conclusion that it was impossible to draw conclusions about the relative merits of the drugs from CATIE's findings (1,(68)(69)(70)(71). These flaws included allowing patients to remain on the same drug they had been receiving prior to randomization, which affected many of those randomized to risperidone or olanzapine (9), and olanzapine dosage up to 30 mg/day (9), three times the dose found to be effective for non-TRS (72). None of the other atypical APDs were permitted to exceed the upper limit of the dosages recommended for non-TRS patients.…”
Section: Use Of Atypical Apds In Non-treatment-resistant Schizophreniamentioning
confidence: 84%